2017
DOI: 10.1080/14658011.2017.1399531
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the printing bed temperature on the adhesion of parts produced by fused filament fabrication

Abstract: For parts produced by fused filament fabrication (FFF) the adhesion between the first printed layer and the printing bed is crucial, since it provides the foundation to the subsequent layers. Inadequate adhesion can result in poor printing quality or destroyed bed surfaces. This study aims at understanding and optimising the adhesion process for parts produced by FFF. The consequences of varying printing bed temperatures on the adhesion of two commonly used printing materials on two standard bed surfaces were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 220 publications
(154 citation statements)
references
References 16 publications
3
149
0
2
Order By: Relevance
“…Hence, the first layer thickness could be decreased in the present work due to a reduced risk of welding (Section ). Consequently, the adhesion increased and therefore the warpage of the printed part decreased …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Hence, the first layer thickness could be decreased in the present work due to a reduced risk of welding (Section ). Consequently, the adhesion increased and therefore the warpage of the printed part decreased …”
Section: Resultssupporting
confidence: 88%
“…Consequently, the adhesion increased and therefore the warpage of the printed part decreased. [92] The incorporation of spherical glass spheres, independent of the size, tends to minimize the warpage compared to neat PP. For the composites printed at a T Ch of 25 °C, drastic differences in their warpage can be discerned (Figure 10c,e,g).…”
Section: Impact Propertiesmentioning
confidence: 99%
“…Several individual research groups discovered that the first layer adhesion to the build platform is one of the main process limitations of PP . It was found that PP does not adhere to standard ME‐AM build platform substrates, such as glass mirrors or polyimide tapes, mainly due to the material's lack of surface functional groups, low surface energy, and low polarity . In order to counteract a possible delamination of the first deposited layer, most researchers recommend to deposit PP‐based filaments onto PP substrates .…”
Section: Processing Of Neat Pp By Me‐ammentioning
confidence: 99%
“…If the adhesion is too good, especially at room temperature, the final product cannot be removed from the platform without damaging the part, the platform, or both . In an ideal process, the part is processed at high adhesion between the first layer and the platform, controllable, for example, through the temperature of the build platform, whereas the part removal is conducted at a state of low adhesion . The type of platform material and the corresponding process parameters heavily depend on the filament material used.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to semi-crystalline 3D-printed materials, where shrinkage can be a severe issue, [45][46][47][48] no warpage of the 3D-printed specimens was observed, as long as sufficient first layer adhesion was guaranteed. [27,49] Therefore, the adhesive spray Dimafix (DIMA 3D, Spain) was applied to the glass mirror. Five specimens were produced per print.…”
Section: Processingmentioning
confidence: 99%